Transisi Kepemudaan dalam Pilihan Karier: Studi Musisi Do it Yourself (DIY) di Kota Purwokerto - Abiyyu, Dany Farhan; Mutahir, Arizal; Rizkidarajat, Wiman; Hariyadi, Hariyadi (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
Career choice among Indonesian youth does not occur autonomously but is shaped through negotiation with the surrounding social environment, particularly families that continue to regard formal employment as the primary marker of stability and success. This complexity becomes more pronounced when young people pursue non-conventional career paths such as do-it-yourself (DIY) music, which offers creative autonomy yet is marked by economic uncertainty. This article examines how DIY musicians in Purwokerto navigate their transition into the labour market, negotiate career choices with their families, and develop adaptive strategies to ope with structural constraints and dominant formal-work norms. Employing a descriptive qualitative method with a case study approach and informed by Karl Mannheim’s theory of social generations, data were collected through in-depth interviews and participant-as-observer, observations involving DIY musicians aged 20-24 who are still enrolled in higher education, additional informants who have completed the transition phase, and parents of the main informants. Data were analyzed using Miles and Huberman’s interactive model with source triangulation. The finding reveal that DIY youth transitions involve ongoing negotiation between creative aspirations, familial expectations, and limitations within the local music ecosystem, addressed through adaptive strategies combining creative labour, paid work, and collective networks.